(3GdfXGe GdbGfhfj dYbO GdQgf GdHMQj (B: s (3OQGSI ebGQfI HGdTQjYI GdESdGejI (B/ s - (3QaGYj eMeO SdjeGf CHhRjO aQGL Ydis; (3SGei YHOGdHGbj CHhUGdM s; (3YHOGdYRjR QeVGf Sec s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3ef NdGd eG SHb jecf Gdbhd (B- (3HCf HMK hOQGSmI YbO GdQgf GdHMQi aj GdbGfhf hGdabg GdESdGej(B: (3bO JfGhdJg aj aUd JegjOj Yf GdQgf HUag YGeI cCOGI ef COhJ GdVeGf hGdGSJjKGb(B: (3Ke HOCJ aMhi OQGSI GdehVhY ef NdGd JcQjS KdGKI CHhGH(B. (3JfGhd GdChd ajgG(B: (3MbjbI GdQgf GdHMQj ef MjK WHjYJg GdJj JHMK aj YbOg hJGQjNg GdJTQjYj(B: (3hPdc dCf gPG GdQgf dG jQO EdnqG Ydi GdSajfI GdHMQjI HeYfGgG GdbGfhfj(B: (3hgPg GdSajfI (B{u(32013(B} (3JeKd aj eLehY JbSje GdCehGd eGdG efbhdG dG jUdM HgPg GdWHjYI dCf jchf eMdkG dgPG GdQgf (B{u(32013(B} (3GdPi dG jJLQO ajg GdQGgf Yf MjGRI SajfJg GdeQghfI(B: (3hdcf gPg GdSajfI CUHMJ GdBf PGJ bjeI GbJUGOjI gGFdI hJSeM ddeTQY HEecGf JbQjQ Qgf jTHg Qgf GdYbGQ QSejG aj GdbGfhf GdeOfj fXQkG dbOQJgG Ydi GdJYjjf hGdJaQjO HeG jSeM HJSLjd GdMbhb GdhGQOI YdjgG(B: (3hde CfS aj fgGjI gPG GdHGH Cf CJfGhd MbjbI gPG GdQgf aj Gdabg GdESdGej cQgf ZjQ ebHhV Jcajg GdQSejI hGdTgQ ddbjGe ebGe GdbHV GdMbjbj(B. (3adeG hVMJ GdacQI GdMbjbjI ddQgf GdHMQj cGf ef GdVQhQj Cf CJfGhd GdYbO GdefTF dg ef MjK ehVhYg hTcdg, hPdc HWQjbI GdehGRfI Hjf GdbGfhf GdhVYj hGdabg GdESdGej Ohf GdJbjO HYed aUhd Ch eHGMK eSJbdI dcd efgeG EdG EPG OYJ VQhQI GdHMK dPdc(B. (3hHYO Cf GSJbQ GfYbGO GdYbO aj Tcdg hehVhYg hJeGKd ddfaGP HbjOg (B{u(32013(B} (3QMJ CNUU GdHGH GdKGdK dBKGQ gPG GdQgf ajeG Hjf WQajg hYdi ZjQge ef GdPjf jVGQhf ef hLhO YbO GdQgf GdHMQj s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2015(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B615-675s
Keywords: (3GdQgf GdMjGRj s; (3GdeGd GdeQghf aj GdbGfhfs; (3GdeGd GdeQghf aj Gdabg GdESdGejs; (3YbO GdbQV GdHMQj s; (3JWgjQ GdSajfI GdeQghfI ef GdOjhf s; (3Qgf GdSajfI GdeedhcI Ydi GdTjhY s; (3Mb GdQGgf s; (3eMceI GSJFfGa QhGf GdaQfSjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs